Malaysia's electricity market structure in transition - Sibeperegasam M.; Ramachandaramurthy V.K.; Walker S.; Kanesan J. (Elsevier Ltd, 2023)
electricity supply; energy market; monopoly; reform process; sustainability; Malaysia